Scientific computing with Python : high-performance scientific computing with NumPy, SciPy, and pandas /: high-performance scientific computing with NumPy, SciPy, and pandas. (2021) - Führer, Claus; Verdier, Olivier; Solem, Jan Erik
No abstract available